Design and in-vitro Evaluation of Float-adhesive Famotidine Microspheres by using Natural Polymers for Gastroretentive Properties - Mahor, Seema; Chandra, Phool; Prasad, Neelkant (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: In the present investigation a novel oral drug delivery system was developed by combining two different techniques floating and mucoadhesive system so called floatadhesive, in order to obtain a controlled system that could remain in the stomach for prolonged period and release the drug in a controlled manner. Materials and Methods: Microspheres containing Famotidine were prepared by ionic gelation method using Mimosa pudica seed mucilage as a natural mucoadhesive polymer. Sodium alginate (SA) and chitosan (CS) were incorporated as drug release modifier. The microspheres were characterized by scanning electron microscopy and evaluated by employing shape and particle size, % drug entrapment efficiency, in vitro floating ability, in vitro mucoadhesion and in vitro drug release pattern. Results: The prepared microspheres were acceptably spherical with a mean particle size in the range of 334 ± 1.18 μm to 498 ± 1.12 μm. Drug entrapment efficiency was observed in the range of 72.82 ± 1.10% to 92.38 ± 1.20%. Formulations containing a combination of both mucilage and chitosan showed increased in vitro mucoadhesion and buoyancy as compared to formulations containing chitosan alone. In vitro drug release for all the formulations in 0.1N HCl was diffusion controlled gradually throughout 12 h and followed Higuchi’s and Korsmeyer Peppas kinetics. The mechanism of in vitro drug release was non-fickian type controlled by swelling and relaxation of the polymer. Conclusion: The developed microspheres have dual advantages of being floating and mucoadhesive to increase oral bioavailability and releasing drug in a controlled manner, to reduce the required frequency of administration thereby promoting patient compliance.
Keywords: Natural polymers; Mimosa pudica mucilage; Chitosan; Floating; Mucoadhesive; Float-adhesive; Ionic gelation